Households Large and Small: Healthcare Civilians and the Prominence of Women’s Work in the Edmonton Bulletin’s Reporting of the 1918 Influenza Pandemic - Wagner, Suzanna (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2022)
Between October and December 1918, more than 10 percent of Edmonton’s population contracted epidemic (or “Spanish”) influenza. The high rates of infection in the city prompted the development of a grassroots system of volunteers to provide support for those affected by the epidemic. Organizers of this volunteer-run relief system recognized that the impact of the flu extended beyond the need for nurses at the sickbed. It encompassed other aspects of household labour, including laundry, cooking, and childcare. Reflecting the domestic needs of Edmonton’s stricken population, healthcare civilians organized their work through household-style cooperatives. This paper examines how the household became the unit of measure commonly employed in the Edmonton Bulletin daily newspaper to conceptualize the impact of, and responses to, the epidemic. Gendered chores, rarely discussed in the newspaper before the epidemic, suddenly merited significant column space. As the perceived importance of domestic labour increased, so did women’s claim to positions of authority and leadership in these newly formed households. The value placed on gendered household chores resulted in both an affirmation of gender roles and a partial, but significant, inversion of gendered authority structures. Women’s flu-time volunteer work was viewed as an act of citizenship during a community crisis, an understanding supported by the conceptual links between wartime military nursing and the public nature of healthcare civilians’ labour.